Wnt/β‐catenin signaling controls intrahepatic biliary network formation in zebrafish by regulating notch activity. Issue 6 (19th April 2018) - So, Juhoon; Khaliq, Mehwish; Evason, Kimberley; Ninov, Nikolay; Martin, Benjamin L.; Stainier, Didier Y.R.; Shin, Donghun
Abstract : Malformations of the intrahepatic biliary structure cause cholestasis, a liver pathology that corresponds to poor bile flow, which leads to inflammation, fibrosis, and cirrhosis. Although the specification of biliary epithelial cells (BECs) that line the bile ducts is fairly well understood, the molecular mechanisms underlying intrahepatic biliary morphogenesis remain largely unknown. Wnt/β‐catenin signaling plays multiple roles in liver biology; however, its role in intrahepatic biliary morphogenesis remains unclear. Using pharmacological and genetic tools that allow one to manipulate Wnt/β‐catenin signaling, we show that in zebrafish both suppression and overactivation of Wnt/β‐catenin signaling impaired intrahepatic biliary morphogenesis. Hepatocytes, but not BECs, exhibited Wnt/β‐catenin activity; and the global suppression of Wnt/β‐catenin signaling reduced Notch activity in BECs. Hepatocyte‐specific suppression of Wnt/β‐catenin signaling also reduced Notch activity in BECs, indicating a cell nonautonomous role for Wnt/β‐catenin signaling in regulating hepatic Notch activity. Reducing Notch activity to the same level as that observed in Wnt‐suppressed livers also impaired biliary morphogenesis. Intriguingly, expression of the Notch ligand genes jag1b and jag2b in hepatocytes was reduced in Wnt‐suppressed livers and enhanced in Wnt‐overactivated livers, revealing their regulation by Wnt/β‐catenin signaling. Importantly, restoring Notch activity rescued the biliary defects observed in Wnt‐suppressed livers. Conclusion: Wnt/β‐catenin signaling cell nonautonomously controls Notch activity in BECs by regulating the expression of Notch ligand genes in hepatocytes, thereby regulating biliary morphogenesis. (Hepatology 2018;67:2352‐2366).